Decreasing stress and supporting emotional well-being among senior nursing students: A pilot test of an evidence-based intervention. (May 2019) - Beanlands, Heather; McCay, Elizabeth; Fredericks, Suzanne; Newman, Kristine; Rose, Donald; Santa Mina, Elaine; Schindel Martin, Lori; Schwind, Jasna; Sidani, Souraya; Aiello, Andria; Wang, Angel
Abstract: Background: Nursing students can experience stress related to their academic and practice experiences, which can have deleterious effects on physical and emotional well-being. Objectives: To pilot test an evidence-based intervention, Dialectical Behavior Therapy-Skills Group, designed to promote emotional well-being among nursing students. Design: A single group, pre-posttest design, mixed-method approach. Setting: A large university situated in a multicultural urban setting. Participants: Senior undergraduate nursing students (n = 31). Methods: Students participated in an 8-week modified Dialectical Behavior Therapy-Skills Group (DBT-SG) intervention. Quantitative and qualitative data were collected to explore the interventions' feasibility, acceptability, and students' perceptions of its applicability to practice. Students also completed standardized outcome measures of psychological distress and emotional well-being pre- and post-intervention to evaluate preliminary effectiveness. Results: Overall feedback was positive, with participants describing how skill modules helped them establish relationships and manage stress in clinical, academic, and personal settings. Significant reductions in stress and improvements in well-being were also reported. Conclusion: Results suggest that DBT-SG offers a promising approach for mitigating nursing students' stress by helping them acquire practice-relevant strengths and self-care strategies. Further research is required to examine the effectiveness of DBT-SG among other nursing student groups, as well as to explore optimal approaches to delivering this intervention in conjunction with nursing curricula.